AT2 receptor interacting protein 1 (ATIP1) mediates COX-2 induction by an AT2 receptor agonist in endothelial cells - Soda, Keita (Biochem Biophys Rep, 2020)
Angiotensin II (Ang II) type 2 receptor (AT2R) is one of the major components of the renin-angiotensin-aldosterone system. Nevertheless, the physiological role is not well defined compared to the understanding of the Ang II type 1 receptor (AT1R), which is a well characterized G-protein coupled receptor in the cardiovascular system. While the AT2R signaling pathway remains unclear, AT2 receptor interacting protein 1 (ATIP1) has been identified as a candidate molecule for interacting with the C-terminal region of AT2R. In this study, we investigated the ATIP1 dependent AT2R inducible genes in human umbilical vein endothelial cells (HUVECs). CGP42112A, an AT2R specific agonist, resulted in an upregulation of inflammatory genes in HUVECs, which were inhibited by knocking down ATIP1 with siRNA (siATIP1). Among them, we confirmed by quantitative PCR that the induction of COX-2 mRNA expression was significantly downregulated by siATIP1. COX-2 was also upregulated by Ang II stimulation. This upregulation was suppressed by treatment with the AT2R specific antagonist PD123319, which was not replicated by the AT1R antagonist telmisartan. These findings suggest that ATIP1 plays an important role in AT2R dependent inflammatory responses. This may provide a new approach to the development of cardio-protective drugs.